PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN KURIKULUM MERDEKA BELAJAR DI ERA DIGITAL - Cahaya Cahaya (Jurnal Bilqolam Pendidikan Islam, 2022)
The "Freedom of Learning" policy was the idea of ​​the Minister of Education and Nadiem Makarim's culture in order to improve the national education system The concept of "Freedom of Learning" is an attempt to realize independence in thinking. Islamic Religious Education as a series of Islamic subjects is delivered both formally in schools or informally and non-formally at home and in the community with the material taught from elementary school to university levels must respond to this Free Learning policy well. Using library research methods, it is obtained the conclusion that Islamic Religious Education Learning version "Merdeka Belajar" is designed to train students to have the ability to think critically, have creativity, have the ability and communication skills and make students have cooperation and be able to collaborate so that later students can have more mature thinking , wiser, more careful so that students are able to understand, develop and apply the teachings Islam in everyday life.